TEACHING READING COMPREHENSION USING STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) - Suyasti, Yeti; Sada, Clarry; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The main purpose of this research is to improve students’ reading comprehension by using Student Teams Achievement Divisions (STAD) cooperative learning. This learning model was done to overcome the weaknesses of teaching learning process in the classroom. STAD is an attractive alternative to teacher-centered instruction which promote the student’s learning by creating maximum opportunity for communicative and meaningful classroom interaction. It consists of five major components: class presentation, teamwork, quizzes, individual improvement score, and team recognition. The researcher conducts this classroom action research in three cycles which involved 35 students. The observation checklist, questioners and test are used to collect the data. In the first cycle, the students’ average score was 49.57. Second cycle, the students’ average score was 70.43 and in the third cycle, the students’ average score increased significantly to 81.71. The conclusion, the use of STAD improves the students’ reading comprehension and their involvement in active learning. Keywords: Reading Comprehension, STAD. Abstrak: Tujuan utama dari penelitian ini adalah untuk meningkatkan pemahaman siswa dalam membaca dengan menggunakan pembelajaran kooperatif STAD. Model pembelajaran ini dilakukan untuk mengatasi kelemahan dalam proses belajar mengajar di dalam kelas. STAD merupakan sebuah model pembelajaran alternatif yang menarik bagi pengajaran yang berfokus pada guru yang mengedepankan pembelajaran siswa dengan menciptakan kesempatan maksimal untuk berkomunikasi dan berinteraksi secara berarti di dalam kelas. STAD memiliki 5 komponen utama: presentasi kelas, kerja kelompok, quiz, peningkatan nilai individu, dan penghargaan kelompok. Peneliti melaksanakan penelitian tindakan kelas dalam tiga siklus dengan melibatkan 35 siswa. Lembar observasi, kuesioner dan tes digunakan sebagai alat pengumpul data. Pada siklus pertama, nilai rata-rata siswa adalah 49.57. Pada siklus kedua, nilai rata-rata siswa menjadi 70.43 dan pada siklus ketiga, nilai rata-rata ini meningkat secara signifikan menjadi 81.71. Kesimpulannya adalah penggunaan model pembelajaran kooperatif STAD dapat meningkatkan pemahaman siswa dalam membaca serta meningkatkan peran siswa dalam pembelajaran aktif. Kata Kunci: Pemahaman bacaan, STAD.